The Significance Of Decorative-Applied Art In The Educational Process Of Higher Education - M.B., Sulaymanova; A.S., Musinova; N.A, Kodirova; N.A, Kodirova; O.N., Shomurodov; Sh.I, Ibadullayeva (The journal of contemporary issues in business and government, 2021)
In the following article the significance of decorative-applied art in the educational process of higher education is analyzed based on the comparative data derived from different sources. The higher educational system of Uzbekistan is intensifying its efforts to consolidate the innovational technologies in the decorative art such as 5 Cutting- Edge Innovations, Decoration Technology of Tableware and others. Uzbek traditional technologies of decorative-applied art passes through the generations is indicated based on the relations of master and disciple.